Application of Material Unlawful Nature in Judges' Decisions at the Jakarta Corruption Court: Penerapan Sifat Melawan Hukum Materiil dalam Putusan Hakim di Pengadilan Tipikor Jakarta - Ulhaq Adhiyaksa (Unnes Law Journal, 2012)
This study aims to determine the nature of the application against the Law of the Material in the study of corruption in Indonesia criminal law; know the judges of the unlawful nature of the material in the court verdict corruption; Research using a normative juridical research methods in the Corruption Court verdict in Jakarta in contradiction with the Constitutional Court decision No.003 / Puu-IV / 2006 in order of criminal justice practices. These results indicate that the judge in applying the law against nature in a positive function of first doing in-depth study and really explore whether the act was an act that is considered evil and disgraceful for the public. The judge looked at the nature of the unlawful nature of the material should be considered against the law in a negative function, not only in a positive function, so that the deeds done while fulfilling the formulation of the offense but not against the law of the negative material can be used as a justification that does not harm the state, not profitable own natural self, others and the legal obligations of the corporation and not subject to criminal prosecution against the perpetrators.